PELATIHAN PERPAJAKAN & PENGISIAN E-SPT (UNTUK GURU DAN PELAKU USAHA KECIL MENEGAH JAKARTA) - Indra Saputra; Fanny Rahmadhitya (Bajang Institute, 2021)
Taxes are the largest source of state income nowadays. However, public compliance in paying and reporting taxes is still relatively low. Therefore, education and training as well as an understanding of taxation procedures are needed from an early on. The purpose of this Community Service (PKM) is to increase knowledge and competence in the field of taxation, especially in understanding the calculation and filling of personal and corporate tax returns, the participants of this community service activity are teachers and small and medium businesses in DKI Jakarta. There is education and training in the form of filling out the Personal and Corporate Taxpayer SPT Forms to improve tax competence. In this digital era, all tax administration has been carried out online so that pre-participants can independently report online taxes. The method or method used in this Community Service Activity is the first to use online through a digital platform, namely zoom meeting. The evaluation is carried out by providing a simulation of filling out the SPT and an assessment with several aspects, namely: (1) the reaction is a response from each participant whether the participant shows interest and activity during the training (2) the learning process, namely all participants take part in the training starting from the beginning to the end (3 ) behavior through the practice of the material provided (3) results in the form of increasing participants' understanding by answering questions.